The importance of entrepreneurship and the situation in Portugal - Gaspar, Fernando (2010)
A study on the published bibliography is developed on the importance of entrepeneurship in the economies of the XXI centuary, in which four areas of relevance are deducted. In the development of the current economies,entrepeneurship assumes an importance increased by four motives: it contributes to the creation of job, it contribute to innovation, it increases the creation of wealth and contributes to the development of the economy and of the society and,finally, it constitutes an ever growing option of career for a great deal of workforce.